Investigasi Ekspor Pakaian Jadi Indonesia: Daya Saing, Determinan, dan Barier - Fadhilah, Muhammad Arief; Widyastutik; Hermawan, Iwan (National Research and Innovation Agency, 2024)
Indonesia's apparel exports are essential for national economic growth. However, compared to the two main exporting countries, China and Vietnam, Indonesia's apparel exports volume is still considered underwhelming. It is because of a high dependence on imported raw materials and trade barriers imposed by partner countries. This research aims to analyze the performance, determinants, and to estimate nontariff measures (NTMs) to Indonesian apparel exports in 11 major export destinations with an analysis period of 2003-2022. The methods used in this research include descriptive analysis, panel data regression with a gravity model, and estimation of equivalent tariffs. The results of the panel data regression show that the importing country's Gross Domestic Product (GDP) per capita, economic distance, tariffs, exporting country's real exchange rate, and export prices significantly affect the volume of apparel exports from the exporting country. Meanwhile, the analysis of dummy variables indicates differences before and after the Free Trade Agreement (FTA) and the Covid-19 pandemic. This study also found that export destination countries impose non-tariff barriers on the volume of Indonesian apparel, as indicated by high equivalent tariff values in some countries.